2020
DOI: 10.1542/hpeds.2019-0244
|View full text |Cite
|
Sign up to set email alerts
|

Discharge Criteria Decrease Variability and Improve Efficiency

Abstract: BACKGROUND AND OBJECTIVES: To determine the effect of discharge criteria on discharge readiness and length of stay (LOS). Discharge inefficiency is a common barrier to hospital flow, affecting admissions, discharges, cost, patient satisfaction, and quality of care. Our center identified increasing discharge efficiency as a method to improve flow and better meet the needs of our patients. METHODS: A multidisciplinary team was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Hospitals have trialed several different initiatives to improve the efficiency of patient discharges, including implementation of discharge criteria for common diagnoses, use of communication boards, and computer applications to facilitate the discharge process, all with varying levels of success. 11,12 Mathews et al, for instance, describe an electronic medical record prompt that identified the likelihood of a patient's next day discharge as red (unlikely), yellow (possible), or green (likely). 11 Although the tool helped to facilitate discharges, it was reliant on the physicians to accurately predict and facilitate hospital discharges.…”
mentioning
confidence: 99%
“…Hospitals have trialed several different initiatives to improve the efficiency of patient discharges, including implementation of discharge criteria for common diagnoses, use of communication boards, and computer applications to facilitate the discharge process, all with varying levels of success. 11,12 Mathews et al, for instance, describe an electronic medical record prompt that identified the likelihood of a patient's next day discharge as red (unlikely), yellow (possible), or green (likely). 11 Although the tool helped to facilitate discharges, it was reliant on the physicians to accurately predict and facilitate hospital discharges.…”
mentioning
confidence: 99%
“…Due to individual centres using different ICPs, this study did not specify individual discharge criteria. One study did not list participant numbers 16…”
Section: Resultsmentioning
confidence: 99%
“…Similar to Shadman et al and Sheft et al, we were able to demonstrate that protocol implementation resulted in improved adherence to clinical recommendations for children with bronchiolitis and resulted in shorter length of stay. 18,19 According to Scheft et al, strategies including the creation of specific discharge criteria within institutions as well as embedding the discharge criteria into daily notes can aid in improving adherence to protocols and recommendations. These strategies can empower physicians to discharge earlier when discharge is safe and appropriate.…”
Section: Discussionmentioning
confidence: 99%
“…These strategies can empower physicians to discharge earlier when discharge is safe and appropriate. 19 In addition, studies are required to evaluate whether nursing-led discharge would result in a change in culture around discharge planning in addition to stricter adherence to policy recommendations with a corresponding reduction in length of stay. These measures are important to consider, as timely discharges are beneficial to health-care systems by improving financial and resource efficiency and allowing more efficient bed turnover.…”
Section: Discussionmentioning
confidence: 99%